AB1014 Comparison between Arashi Score and Modified Total Sharp Score in The Evaluation of Large Joints Destruction in Patients with Rheumatoid Arthritis under Disease Control of Biologic Disease Modifying Anti-Rheumatic Drugs. (15th July 2016) - Hashizume, K.; Nishida, K.; Nasu, Y.; Nakahara, R.; Machida, T.; Horita, M.; Takeshita, A.; Kaneda, D.; Natsumeda, M.; Ezawa, K.; Ozaki, T.
Abstract : Background: Treatment of rheumatoid arthritis (RA) has improved over the past decade with the modification of treatment strategy and recent application of biologic agents (Bio). It has been revealed that the treatment by Bio achieved not only improvement of clinical symptom, but also inhibition of the progression of joint destruction in small joints of hand and foot. However, there are little evidences of inhibition of the progression of the large joint destruction with the treatment by Bio. ARASHI score, is composed of ARASHI Status Score (ASS) and ARASHI Change Score (ACS), and have been newly developed to evaluate the progression of the large joint destruction as well as remodeling 1) Objectives: We aimed to investigate the correlation among the ARASHI score, modified total sharp score (mTSS), and other clinical parameters, and to clarify the patients' parameters leading to large joint destructions in patients with RA under disease control by Bio. Methods: 75 patients with RA under disease control by Bio were available for the current study. Average patients' age, disease duration, and follow-up periods were 62.6 (years old), 11.7 (year), and 21.8 (month), respectively. They were examined for serum level of C-reactive protein (CRP), mHAQ, DAS28-CRP, SDAI, CDAI, mTSS, and ASS at the beginning of the study. The amount of change of CRP, mHAQ, DAS28-CRP, SDAI, CDAI, and mTSS at the final follow-up were defined as ΔCRP, ΔmHAQ, ΔDAS28-CRP, ΔSDAI, ΔCDAI, and ΔmTSS, respectively. Statistical analysis was performed by Spearman's correlation co-efficient. Results: Average ΔCRP, ΔmHAQ, ΔDAS28-CRP, ΔSDAI, ΔCDAI, ΔmTSS, and ACS were 0.01, -0.02, -0.28, -2.62, -2.64, and 0.03, respectively. There was no significant correlation between the ACS and ΔmTSS. There were no significant correlations between ΔmTSS and other clinical parameters, whereas ACS was significantly correlated with ΔCRP (r=0.39), ΔmHAQ (r=0.28), ΔDAS28-CRP (r=0.39), ΔSDAI (r=0.35), and ΔCDAI (r=0.32). Conclusions: The correlation between the destruction of small joints of hands and feet and the disease activity was not seen among the current patients group with long-standing disease. In contrast, our results suggested that sufficient suppression of the disease activity is important to prevent the progression of large joint destruction among long-standing RA patients under control by Bio. References: Kaneko A, et al., Mod Rheumatol. 2013;23:1053–62 Disclosure of Interest: None declared